Has the application of sanctions against financial institutions involved in money laundering had a deterrent effect? - Hasan Basri; Harly Clifford Jonas Salmon; Judy Marria Saimma (PT. Anagata Sembagi Education, 2024)
Money laundering is one of the crimes that has a wide impact, both economically and socially. With the increasing complexity of global financial networks, financial institutions must be more responsible in preventing money laundering practices. The existence of strong and transparent financial institutions is essential to maintain the integrity of the financial system. Using normative juridical research methods, this study analyzes the regulations that govern sanctions and law enforcement practices. The purpose of this study is to evaluate whether the sanctions applied have provided a deterrent effect to financial institutions that violate the law. The results of the study show that although there are several institutions affected by sanctions, in general, the implementation of sanctions has not been effective in providing a significant deterrent effect. These obstacles arise due to the lack of strict supervision, weak international cooperation, and inconsistencies in law enforcement. In addition, the proactive attitude of financial institutions in fulfilling reporting obligations also needs to be improved. Therefore, reforms in the sanctions system and improved law enforcement mechanisms are needed to create a stronger deterrent effect against financial institutions involved in money laundering